2021
DOI: 10.1177/03000605211015079
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the optimal dose of low ionizing radiation to enhance immune function: a rabbit model

Abstract: Primary liver cancer is one of the most common malignant tumors in China. Currently, immunotherapy for liver cancer is a research hotspot. Experimental studies and epidemiological investigations have confirmed the antineoplastic activity of low ionizing radiation. The aim of this study was to explore the optimal dose of low ionizing radiation to enhance immune function. Twenty-five New Zealand rabbits were randomly divided into five groups (n = 5 each): experimental group 1 (25 mGy), experimental group 2 (50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that cancer patients with obesity have a higher radiotherapy resistance in clinical settings ( Sabol et al, 2020 ), indicating that a HFD-related life style is not only a risk factor associated with many diseases but may also play a role in the development of diseases combined with other environmental factors. Radiation exposure, a common environmental physical factor known for its double-edged ability to provide beneficial or non-beneficial outcomes, is used in medical diagnosis or therapy and can improve the liver immune function at low radiation doses ( Zhang et al, 2021a ). However, there is also a risk of oxidative liver damage after frequent high doses of radiotherapy ( Sharma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cancer patients with obesity have a higher radiotherapy resistance in clinical settings ( Sabol et al, 2020 ), indicating that a HFD-related life style is not only a risk factor associated with many diseases but may also play a role in the development of diseases combined with other environmental factors. Radiation exposure, a common environmental physical factor known for its double-edged ability to provide beneficial or non-beneficial outcomes, is used in medical diagnosis or therapy and can improve the liver immune function at low radiation doses ( Zhang et al, 2021a ). However, there is also a risk of oxidative liver damage after frequent high doses of radiotherapy ( Sharma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%